1998
DOI: 10.1016/s0010-8804(98)80298-x
|View full text |Cite
|
Sign up to set email alerts
|

Reach out and touch your customers

Abstract: [Excerpt] This study of 105 dining parties at a casual chain restaurant found that a male server received significantly larger tips when he touched the shoulder of the person paying the bill than when he did not touch the customer. This touch effect on tips was essentially the same whether the touch was for two or four seconds, and whether the customer being touched was male or female. The age of the customer, however, did have a significant effect on the extent to which the touch increased the server's tips. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 0 publications
1
16
0
3
Order By: Relevance
“…Description of relevant studies. The search described in the previous section uncovered three published (Lynn & Graves, 1996;Lynn et al, 1998;Mok & Hansen, 1999) and two unpublished4 (Conlin, Lynn, & O'Donoghue, 2003;Lynn, 2000b) academic studies that provided the sought-after information about ethnic differences in tipping and that was available for inclusion in this analysis. We are aware of three additional studies that will be coming out in the near future, but those data sets are not available for analysis at this time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Description of relevant studies. The search described in the previous section uncovered three published (Lynn & Graves, 1996;Lynn et al, 1998;Mok & Hansen, 1999) and two unpublished4 (Conlin, Lynn, & O'Donoghue, 2003;Lynn, 2000b) academic studies that provided the sought-after information about ethnic differences in tipping and that was available for inclusion in this analysis. We are aware of three additional studies that will be coming out in the near future, but those data sets are not available for analysis at this time.…”
Section: Methodsmentioning
confidence: 99%
“…These studies employed one of two methodologies. Two of the studies (Lynn, 2000b;Lynn et al, 1998) had restaurant servers record information about their customers, including information about the customers' bill sizes, tips, and apparent ethnicities. The other three studies (Conlin et al, 2003;Lynn & Graves, 1996;Mok & Hansen, 1999) had students interview restaurant customers as they were departing the restaurant.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, people often adjust their actual tips up or down from the calculated tip percentages, and those adjustments appear to be spontaneous and at least partially outside of conscious control. For example, researchers have found that tips are affected by how sunny it is outside (Cunningham, 1979;Rind, 1996), whether or not the server touches the customer (Crusco & Wetzel, 1984;Lynn, Le, & Sherwyn, 1998), and whether or not the server repeats the customer's order (van Baaren, Holland, Steenart, & van Knippenberg, 2003). These factors are unlikely to be part of customers' conscious deliberations about how much to tip (see van Baaren et al, 2003), so tipping is affected by unconscious as well as conscious processes.…”
Section: Potential Explanationsmentioning
confidence: 99%
“…Tipping has been the subject of numerous studies in social psychology and other disciplines (for a review, see Lynn, 2006). Much of this research has examined the effects on tipping of service (Lynn, 2003;Lynn & McCall, 2000) and of specific server behaviors, such as smiling at customers (Tidd & Lockard, 1978), touching customers (Crusco & Wetzel, 1984;Hornik, 1992;Lynn, Le, & Sherwyn, 1998), giving customers candy (Strohmetz, Rind, Fisher, & Lynn, 2002), squatting down next to the table (Davis et al, 1998;Lynn & Mynier, 1993) and writing or drawing on the check (Rind & Bordia, 1995, 1996Rind & Strohmetz, 1998, 2001.…”
mentioning
confidence: 99%